Charge Coupled Devices as Particle Detectors - Dan A. Iordache; Paul E. Sterian; Ionel Tunaru (Advances in High Energy Physics)
As it is well known, while the most important advantages of the charge coupled devices, as high energy particle detectors are related to their (a) extremely high sensitivity (very important for the underground laboratories, also) and (b) huge number of very small independent components (pixels) of the magnitude order of